THE EFFECT OF STUDENT BEHAVIOR ON THE USE OF CAMPUS JOURNALS BY ADOPTING THE TAM METHOD - Asrul Sani; Agusta Pratama Wibawa; Nur Nawaningtyas Pusparini; Adrial Rusyid; Anton Hindardjo (LPPM Nusa Mandiri, 2021)
This research is a quantitative study using statistical analysis based on SEM-PLS in the analysis process. The data collection technique used random sampling where the respondents filled out a questionnaire simultaneously by conducting a structured interview. The number of respondents generated was 203 students from various universities who used website-based campus journals. The Technology Acceptance Model (TAM) is a reference in the model used, on the grounds that TAM is one of the technology acceptance models that are widely adopted in research based on acceptance technology, in this case, the use of website-based campus journals. Initial data processing, coding is carried out adjusted to the data obtained using SPSS, then processing the data using SmartPLS 3.0. The results obtained based on the analysis of measurement models and structural models are that student behavior in using journals gives positive results on the scientific development that they want to obtain from the journal. This is shown from the measurement model testing which shows all indicators accompanying the variables, giving positive results based on convergent validity, discriminative validity, and reliability of the model used. Meanwhile, the structural model testing is calculated based on the path coefficient, determination, predictive relevance, and t-test. The number of path analyses obtained is four, wherefrom the results of data processing, all paths produce significant path coefficients, strong model determination, all pathways produce good predictive relevance, and t-test results for all variables that are interconnected based on pathways. which is formed is acceptable. These results prove that the behavioral effect of using campus journals by adopting TAM as the model used produces positive results